Good manufacturing and hygiene practices in small scaled food processing enterprise: a case study - Wahid, Zaharah; Shohaimi, Anis Syuhaiza; Ahmad, Kartini; Husin, Hafizah (Knowledge Transfer Center, University Sains Malaysia, Pulau Pinang, 2017)
The purpose of this study is to determine the compliance of small food processing enterprise to Good Manufacturing Practices (GMPs) and Good Hygiene practices (GHPs) stipulated by the Ministry of Health, Malaysia. This study has performed an audit at the food processing enterprise in a rural area. The results of the audit report suggested that three major non compliances are found. They are categories into three components; the infrastructure of the premise and facilities, cleanliness of processing equipment and personal hygiene behavior. The study shows that the burden of the adoption of GMP and GHP in small enterprise is the cost. The enterprise has limited basic knowledge of GMP and GHP requirements and unaware of poor hygiene practices can affect the safety and quality of finished product. The most important factor noted during the audit is that the enterprise has excess to the government water supply and stable supply of electricity. Another positive point that the study found is the location of the premise is sited away from flood prone or polluted area suggesting minimal contamination from the environment and less prone to insects and rats infestation. Beside financial constraint, the obstacles that hamper the implementation are knowledge in designing the premise and workers attitude to prevent food safety problems. Effective continuous training intervention program is essential to educate workers to implement personal hygiene practices. Proper implementation of best practices can reduce or prevent the risk of food borne diseases or illness. Therefore, effective knowledge transfer especially to small and medium enterprise could reduce quality rejection rate and increase the customer confidence in their products and increase market opportunities.